Training Needs of Rythu Mitra Group Member in Bt. Cotton Cultivation - Manti, Venkataramulu,; Bahal, Ram (Indian Journal of Extension Education, 2010)
Training is the systematic development of knowledge, skills and attitudes required by an individual to perform adequately for a particular task. With a view to measure the training needs of Rythu Mitra Group members in Bt. Cotton cultivation, the study was conducted in Warangal and Guntur districts of Andhra Pradesh state. Findings revealed that majority of the Rythu Mitra Group members expressed their training needs on recognition of crop damage caused by specific insect pests, manures and fertilizers, soil management, integrated pest management, accurate preparation of sprays and knowledge of insecticide chemical groups and identification of beneficial insects.